Foreign Body Granuloma Following Orbital Reconstruction with Porous Polyethylene. Issue 6 (November 2016) - Timoney, Peter J.; Clark, Jeremy D.; Frederick, Paul A.; Krakauer, Mark; Compton, Christopher; Horbinski, Craig; Sokol, Jason; Nunery, William R.
Abstract : Porous polyethylene is commonly used in the orbit for fracture repair and anophthalmic reconstruction; it reportedly has a good safety profile and integrates well into host tissue. Foreign body reaction to porous polyethylene has been reported in facial tissue, but to our knowledge, not in the orbit. The authors report 2 cases of foreign body inflammatory giant cell reaction in patients who underwent orbital fracture repairs with porous polyethylene implants. Abstract : The authors report of two cases with histologic evidence of foreign body granuloma formation after orbital reconstruction with porous polyethylene.